Regulatory Harmonization: Streamlining Global Pharmaceutical Validation Practices - Devkumar Darshan Rajpuriya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The pharmaceutical industry faces increasing challenges in navigating diverse regulatory frameworks across global markets. This article examines the complexities and opportunities in harmonizing pharmaceutical validation practices across major regulatory bodies, including the FDA, EMA, and ICH. Through analysis of current practices, challenges, and emerging trends, we explore how regulatory harmonization can streamline drug development processes, enhance operational efficiency, and foster innovation while maintaining stringent quality standards. The article covers the implementation of risk-based approaches, standardized protocols, and digital transformation initiatives in validation processes. Furthermore, it evaluates the impact of harmonization on operational efficiency, quality enhancement, and business performance while considering future technological advances and evolving regulatory landscapes.